Evaluation of Employment Policy in Papua Province: Study of Papua Governor's Regulation Number 34 of 2019 Concerning the Organization and Work Procedures of the Department of Industry, Trade, Cooperatives, Small and Medium Enterprises and Labor - Abner Herry Bajari; Sepo Nawipa (International Journal of Scientific Multidisciplinary Research, 2024)
The high unemployment rate in Papua Province, reaching 65,000 people, is one of the main challenges in achieving regional development goals, especially in the employment sector. This unemployment is spread across various districts/cities in Papua and is an obstacle to achieving the targets of the Papua Provincial Government's technical institutions, namely the Department of Industry, Trade, Cooperatives, Small and Medium Enterprises and Manpower (Perindagkop UKM dan Manpower), which is regulated by Gubernatorial Regulation Number 34 of 2019. This regulation only regulates employment matters but does not cover aspects of workforce placement, which should be an important part of reducing unemployment. This research aims to describe and analyze the evaluation of employment policies in Papua Province, especially those related to Gubernatorial Regulation Number 34 of 2019 concerning the organization and work procedures of the Department of Industry and Trade, UKM, and Manpower, and identify the obstacles that exist in implementing these policies. This research uses a qualitative approach with descriptive methods and data collection through in-depth interviews and Focus Group Discussions (FGD) with stakeholders related to employment policies in Papua